2003
DOI: 10.1046/j.1471-4159.2003.01802.x
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid inhibits substance P‐induced activation of protein kinase C epsilon and expression of the substance P receptor

Abstract: The neuropeptide substance P (SP) has been hypothesized to be involved in the etiopathology of affective disorders. This hypothesis is based on the findings that neurokinin-1-receptor antagonists have antidepressant effects in depressed patients and that SP may worsen mood. In this study, we investigated the effect of the mood-stabilizing agents valproic acid (VPA), carbamazepine, and lithium on SP-induced gene expression. As a model system, we used primary rat astrocytes and human astrocytoma cells, which bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…SP can directly stimulate IL-8 gene expression in human astrocytoma U373MG (Lieb et al, 1997) and in NK-1R stably transfected nontransformed human colonocytes (Zhao et al, 2002). Although PKCs (Palma et al, 1995), including PKC␦ (Soltoff and Toker, 1995) and PKC⑀ (Lieb et al, 2003), have been associated with SP/ NK-1R signaling, their involvement in SP-induced colonocyte proinflammatory responses has never been explored. We report here for the first time that SP rapidly and persistently activates PKC␦, and this event is involved in SP-associated activation of the NF-B pathway leading to IL-8 gene transcription.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SP can directly stimulate IL-8 gene expression in human astrocytoma U373MG (Lieb et al, 1997) and in NK-1R stably transfected nontransformed human colonocytes (Zhao et al, 2002). Although PKCs (Palma et al, 1995), including PKC␦ (Soltoff and Toker, 1995) and PKC⑀ (Lieb et al, 2003), have been associated with SP/ NK-1R signaling, their involvement in SP-induced colonocyte proinflammatory responses has never been explored. We report here for the first time that SP rapidly and persistently activates PKC␦, and this event is involved in SP-associated activation of the NF-B pathway leading to IL-8 gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Since SP can transiently stimulate PKC␦ tyrosine (Soltoff and Toker, 1995) and PKC⑀ serine phosphorylation (Lieb et al, 2003), we first examined whether SP activates these as well as other PKC members in human colonic epithelial cells by Western blot analyses using phospho-specific PKC antibodies. To do this, NCM460-NK-1R cells were stimulated with SP (10 Ϫ7 M) for 1 to 60 min, and equal amounts of cell protein were used to determine phosphorylation of various PKCs.…”
Section: Sp Induces Phosphorylation Of Pkc␦ Pkc⑀ and Pkcmentioning
confidence: 99%
See 1 more Smart Citation
“…Substance P is a neuropeptide that is widely distributed throughout the central and peripheral nervous system (Pioro et al, 1990;Dudas and Merchenthaler, 2002;Lieb et al, 2003) and it has been shown to play a role in the pathomechanism of bipolar disorder (Lieb et al, 2003). Substance P regulates the release of acetylcholine in the cortex and co-localizes with dopamine in the midbrain and striatum, with GABA in the cortex, and with serotonin in the raphe nuclei (Jakab et al, 1997).…”
Section: Substance Pmentioning
confidence: 99%
“…Substance P, along with its receptor, the neurokinin 1 receptor (NK1R), is distributed in numerous areas of the brain including hippocampus, amygdala, frontal cortex and hypothalamus, and it appears to be involved in regulating responses to stress and fear (Herpfer and Lieb, 2005). Alterations of substance P content in these regions have been noted to influence the stress response and affective states (Lieb et al, 2003). Administration of substance P produces fear-related behaviors while blockade of NK1/2R or NK1/2/3R is associated with anxiolytic effects (Herpfer and Lieb, 2005).…”
Section: Substance Pmentioning
confidence: 99%